Acute renal failure following oral sodium phosphate bowel preparation: a nationwide case-crossover study - Choi, Nam-Kyong; Lee, Joongyub; Chang, Yoosoo; Kim, Ye-Jee; Kim, Ju-Young; Song, Hong Ji; Shin, Ju-Young; Jung, Sun-Young; Choi, Yukyong; Lee, Jin-Ho; Park, Byung-Joo (Endoscopy, 2014)
Background and study aims: Oral sodium phosphate (OSP) is a cleansing agent for colonoscopy. Recent reports have cited an increased risk of acute renal failure (ARF) in OSP bowel purgative users, but this risk remains under debate. This study was performed to evaluate the association between OSP and ARF in patients who underwent colonoscopy.Patients and methods: A population-based case-crossover study was conducted using the Korean Health Insurance Review and Assessment Service (HIRA) claims data from 1 January 2005 to 31 December 2009. The study population consisted of patients aged ≥ 50 years who underwent colonoscopies after an OSP prescription prior to their first hospitalization for ARF. For each patient, one hazard and four control periods were matched at specified time windows. Conditional logistic regression analysis was used to estimate the odds ratio (OR) and 95 % confidence interval (CI), adjusting for concomitant medications that could induce ARF.Results: A total of 1105 patients were included (54 % male). The adjusted ORs for ARF related to the use of OSP when applying the 1-, 2-, 4-, 8-, or 12-week time windows were 3.7 (95 %CI 2.37 – 5.67), 3.5 (95 %CI 2.45 – 4.89), 3.0 (95 %CI 2.30 – 3.95), 2.4 (95 %CI 1.93 – 2.96), and 2.0 (95 %CI 1.69 – 2.46), respectively. When adopting an 8-week time window, the adjusted OR was 2.5 (95 %CI 1.98 – 3.16) for the subgroup without chronic renal failure.Conclusions: The use of OSP was significantly associated with ARF both in patients with and without co-morbidities.